Correlation between critical properties and magnetocaloric effect using phenomenological model in La0.7Ca0.2Ba0.1MnO3 compound. (October 2017) - Ezaami, A.; Sellami-Jmal, E.; Cheikhrouhou-Koubaa, W.; Cheikhrouhou, A.; Hlil, E.K.
Abstract: This paper presents a theoretical work on magnetic and magnetocaloric properties of La0.7 Ca0.2 Ba0.1 MnO3 powder sample elaborated by high energy ball milling. Using the phenomenological model, the magnetocaloric parameters such as the magnetic entropy change ΔSM and the relative cooling power RCP, have been determined from the magnetization data as a function of temperature at several magnetic applied fields. In addition, from the magnetocaloric results, such as ΔS max  ≈  a ( μ 0 H ) n and Tpeak -TC   ≈  b (μ0 H) 1/Δ, the critical exponents values related to the magnetic transition have been determined. The estimated results are close to those expected by the tricritical mean-field model. Furthermore, using other various techniques (such as the modified Arrott plots, the Kouvel-Fisher method and the critical isotherm analysis), the values of the ferromagnetic transition temperature TC, as well as the critical exponents β, γ and δ are simulated and compared with those obtained by the theoretical model. A good agreement has been found in the vicinity of the Curie temperature. The field and temperature dependent magnetization follow the scaling theory, and all data fall on two distinct branches, one for T < TC and the other for T > TC, indicating that the critical exponents obtained in this work are accurate. Highlights: Using the phenomenological model, the magnetization curves at several magnetic fields were simulated. Critical exponents values have been determined from the magnetocaloric effect results. The estimated results are close to those expected by the tricritical mean-field model. Using various techniques, the critical exponents are simulated and compared with those obtained by the theoretical model.